Quality, during storage, of chicken eggs (Gallus gallus domesticus) coated with oil - Castro-Alvarado, Henry (2023)
Introduction: Eggs are one of the main foods providing nutrients to the world population, however, they rapidly loose quality. For the egg industry it would be beneficial to have technological alternatives to increase the shelf life, such as coatings that are applied to prevent quality loss. Objective: To evaluate the effect of the application of oil coatings on the physicochemical, microbiological, and sensory quality of hen eggs during storage. Methods: We applied, by immersion, coatings of deodorized medicinal grade mineral oil or palm and soybean olein with TBHQ 0,02% to category A Isa Brown hen eggs from a local producer, without prior cleaning, washing or disinfection. After a 6-hour drainage, we stored eggs at 21°C and 43% RH. We measured selected quality parameter every 7 days for a total of 42 days and statically compared trends over time for coated and uncoated eggs. Sensory analysis was also carried out using paired comparisons tests for fresh and coated eggs stored for a certain time. We used a hedonic scale for general acceptance of coated and uncoated eggs after 35 days of storage. Results: The evaluated coatings did not affect the normal behavior of the color and pH of the yolk, the Haugh units, the resistance to rupture and the total aerobic and yeast and mold counts during storage, while retarding the deterioration related to the yolk index, pH of the white and overall mass loss. In addition, the application of the coatings helped keep flavor perception of stored eggs when compared with fresh eggs; resulted in eggs with the same smell and adhesiveness as the uncoated egg; gave shine, and did not negatively influence external sensory acceptance. Conclusion: The shelf life of eggs during storage can be extended with the application of mineral or palm oil coatings.